Megalitic Culture on The Sumberpakem Site Mayang District, Jember Regency - Dian Palupi; Kayan Swastika; Sumarjono Sumarjono; Mohamad Na'im; Akhmad Ryan Pratama; Robit Nurul Jamil (History Education, University of Jember, 2021)
Abstract Megalithic culture in Jember Regency has existed for thousands of years which has been proven by ancient objects on Mount Watangan and the discovery of other archaeological objects at the Sumberpakem Site, Mayang District with different naming and the only finding of the Kangkang stone in Jember Regency. . The problems studied in this research are; How many archaeological remains of megalithic culture at the Sumberpakem Site, Mayang District, Jember Regency? How is it spread? What are the types and functions of the archaeological remains of the megalithic culture? What is the conception of belief that underlies the creation of archaeological remains of megalithic culture at the Sumberpakem Site, Mayang District, Jember Regency? What is the picture of the social and economic life of the community making archaeological remains of megalithic culture at the Sumberpakem Site, Mayang District, Jember Regency?. The research methods used are: heuristics, criticism, interpretation, and historiography. As for the results of this study, the total number of archaeological remains of megalithic culture that was successfully inventoried by researchers at the Sumberpakem Site, Mayang District, Jember Regency, was 7 pieces of which the type of megalith was 2 stone mortars, 1 pictorial monolith, 1 dolmen grave, 3 stone mortars, the conception of belief held by the supporting community is the religious conception of Ancestor Worship that ancestral spirits always protect living relatives. the supporting community has recognized the pattern of permanent housing as a place to live. The existence of graves shows social stratification and differentiation. The affluent economic situation is evidenced by the ability to bury its citizens using dolmen graves and they have an egalitarian pattern. The agricultural subsistence pattern is characterized by the presence of stone mortars, stone mortars and scratched stone monoliths Key words: megalitic, culture, site